Preserving the World Trade Organization's Role Amid the Proliferation of Essential Security Interest - Nivia (Faculty of Law, Universitas Airlangga, 2024)
Abstract International economic regime has been interrupted by recent disputes involving national security exception under Article XXI GATT. Along with the spirit of trade liberalization behind WTO's establishment, the Panel conclude that it has jurisdiction on the matter. Nonetheless, this decision is opposed by several countries. This research aims to consider whether this approach is in line with GATT 1994's purpose, namely to preserve the balance between trade liberalization and security interest of its Member States.Even though the answer is positive, the issue of compliance arises because of politically sensitive nature of security interest. Some States has expressed its refusal to comply with WTO's decision on security interest exception. Hence, there is urgency to consider alternative forum to prevent all cases directly brought to litigation process. This research shows that WTO Panel's approach to exercise its jurisdiction regarding the invocation of article XXI is indeed the best approach to maintain delicate balance between trade liberalization and security interest. However, aside of this adjudicative mechanism, there is proposal to establish National Security Committee to deal with states' interest issue that may affect international trade system. Keywords: essential security exception; World Trade Organization; dispute settlement mechanism. Abstrak Rezim ekonomi internasional terusik oleh beberapa kasus terakhir yang melibatkan pengecualian keamanan nasional di bawah artikel XXI GATT. Bersamaan dengan semangat pembentukan WTO, Panel menyimpulkan bahwa WTO memiliki yurisdiksi dan kasus tersebut dapat diperkarakan. Meskipun demikian, keputusan ini ditentang oleh beberapa negara. Penelitian ini bertujuan untuk menganalisis apakah pendekatan demikian selaras dengan tujuan GATT 1994, yakni menjaga keseimbangan antara liberalisasi dagang dan kepentingan keamanan negara anggotanya. Walaupun jawaban atas pertanyaan tersebut positif, isu kepatuhan muncul karena sensitivitas politis dari isu keamanan. Beberapa negara telah menunjukkan penolakannya untuk patuh pada kepputusan WTO dalam konteks kepentingan keamanan. Maka dari itu, terdapat urensi untuk menimbang alternatif forum lain untuk mencegah semua kasus dibawa ke dalam proses litigasi. Hasil penelitian menunjukkan bahwa pendekatan yang dilakukan WTO dengan menyatakan kewenangan mengadilinya atas artikel XXI memang merupakan pendekatan terbaik untuk menjaga keseimbangan antara liberalisasi perdagangan dan kepentingan keamanan negara anggota. Namun, di samping forum adjudikatif ini, terdapat proposal untuk membentuk National Security Committee untuk menangani isu keamanan negara yang mungkin memengaruhi sistem perdagangan internasional. Kata Kunci: pengecualian keamanan esensial; World Trade Organization; mekanisme penyelesaian sengketa.